TEACHING ENGLISH READING COMPREHENSION AND ITS IMPACT ON 6TH GRADERS’ACHIEVEMENT - Fozia Kanwal; Hina Iqbal; Saleha Ali; Asim Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
In the implementation of reading comprehension, teaching plays a crucial role. Global and national indicators suggest a significant insufficiency in the implementation of reading comprehension, particularly at the elementary school level. This study aimed to gain insights into the factors that influence students’ performance in implementing reading comprehension at the elementary school level. The researchers used an experimental and non-equivalent control group design. The study was conducted with one 6th-grade high school class, with an experimental group of 30 participants and a control group of 29 participants. The researchers developed a pre-test and post-test, which were administered to both groups. The experimental group was then taught using English reading comprehension strategies (pre-reading, during reading, and after reading), while the control group was taught using traditional methods. After a four-week intervention period, the post-test was conducted. The data were analyzed by applied both paired sample t-tests and independent sample t-tests to calculate the significant differences. The researcher concludes that teaching through strategies enhanced students’ understanding levels. The analysis showed no significant difference in pre-test scores between the control and experimental groups. However, a significant difference was found in the post-test scores, with the experimental group outperforming the control group. Furthermore, the experimental group showed a significant improvement in their post-test scores compared to their pre-test scores, while the control group’s post-test scores were lower than their pre-test scores.